Development and Piloting Testing of an Experimental Tobacco and Nicotine Product Marketplace. Issue 7 (11th October 2019) - Carroll, Dana Mowls; Strayer, Lori; Nardone, Natalie; Pacek, Lauren R; Kozink, Rachel V; Tessier, Katelyn; McClernon, Joseph; Benowitz, Neal; Bickel, Warren K; Hatsukami, Dorothy
Abstract: Introduction: We describe the development and pilot testing of the experimental tobacco and nicotine product marketplace (ETM)—a method for studying tobacco and nicotine product (TNP) choices and use behavior in a standardized way. Aims and Methods: The ETM resembles an online store populated with TNPs. Surveillance activities and data from a US representative survey and consumer reports were used to determine the most popular TNPs for inclusion in the ETM. Standardized information and videos demonstrating how to use the TNPs were provided. To test the feasibility of using the ETM, smokers ( n = 119) underwent monitoring of usual brand cigarette smoking and other TNP use (Baseline Phase) followed by access to the ETM (ETM Phase) that included their usual brand cigarettes, e-cigarettes, moist snuff, snus, and nicotine replacement therapy. During the ETM Phase, participants were provided points based on their baseline TNP consumption to exchange for TNPs in the ETM. Participants were advised to exchange points for enough TNPs to last until their next visit and to refrain from using TNPs not obtained in the ETM. A subset of the participants ( n = 62) completed a survey on their experience with the ETM. Results: The majority of the participants stated they were comfortable with navigating the ETM (97%), it was easy to determine product characteristics (89%), and they were satisfied with the products included in the marketplace (85%). Conclusions: The ETM was well received by the vast majority of the participants and can be utilized by researchers to investigate a variety of TNP policy and regulatory science research questions. Implications: Patterns of TNP use are complex due to greater availability, marketing, and promotion of a diverse array of TNPs. Innovative methods are needed to experimentally study TNP choices and patterns. Through describing the development of the ETM, we provide researchers with a tool that can be readily adapted to studying a variety of phenomena challenging public health.